2020
DOI: 10.3390/v12040421
|View full text |Cite
|
Sign up to set email alerts
|

SERTA Domain Containing Protein 1 (SERTAD1) Interacts with Classical Swine Fever Virus Structural Glycoprotein E2, Which Is Involved in Virus Virulence in Swine

Abstract: E2 is the major structural glycoprotein of the classical swine fever virus (CSFV). E2 has been shown to be involved in important virus functions such as replication and virulence in swine. Using the yeast two-hybrid system, we previously identified several host proteins specifically interacting with CSFV E2. Here, we analyze the protein interaction of E2 with SERTA domain containing protein 1 (SERTAD1), a factor involved in the stimulation of the transcriptional activities of different host genes. We have conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Apart from these, the potential roles of TRIP-Brs in BRCA and other cellular processes through several biological pathways, including E2F1 proliferation pathway, neurological process, PI3K/AKT/BRCA1 axis signaling pathway, 56 adenylyl cyclase-mediated cAMP signaling, 12 Nrf pathway, 26 ER stress-induced BAT dysfunction, 57 , 58 BMP/SMAD pathway, 58 reactive oxygen species (ROS)-induced cell death and ubiquitination, 11 , 15 p53 transcriptional and pRb1-cyclin D1-cdk4/6-p16(INK4A) pathway, 59 Toll-like receptor (TLR), induced immune. 18 , 27 , 60 , 61 , 62 Further, this study also revealed the correlation between mRNA levels of TRIP-Brs and immune-infiltrating factors. Thus, TRIP-Brs may also play an essential role in spatial heterogeneity of the tumor microenvironment in patients with BRCA.…”
Section: Discussionsupporting
confidence: 65%
“…Apart from these, the potential roles of TRIP-Brs in BRCA and other cellular processes through several biological pathways, including E2F1 proliferation pathway, neurological process, PI3K/AKT/BRCA1 axis signaling pathway, 56 adenylyl cyclase-mediated cAMP signaling, 12 Nrf pathway, 26 ER stress-induced BAT dysfunction, 57 , 58 BMP/SMAD pathway, 58 reactive oxygen species (ROS)-induced cell death and ubiquitination, 11 , 15 p53 transcriptional and pRb1-cyclin D1-cdk4/6-p16(INK4A) pathway, 59 Toll-like receptor (TLR), induced immune. 18 , 27 , 60 , 61 , 62 Further, this study also revealed the correlation between mRNA levels of TRIP-Brs and immune-infiltrating factors. Thus, TRIP-Brs may also play an essential role in spatial heterogeneity of the tumor microenvironment in patients with BRCA.…”
Section: Discussionsupporting
confidence: 65%
“…Besides, it has been shown that E2 can interact with a wide range of host proteins such as actin, thiredoxin, an-nexin 2, dynactin 6, mitogen-activated protein kinase 2, SERTA domain containing protein 1, etc. [22]. The data obtained by FACS-analysis revealed that the number of cells with a high fluorescence intensity was significantly higher in pTR-EGFP/E2 transfected cells 41.9±13.1 % (of the total cell number) (Fig.…”
Section: Resultsmentioning
confidence: 75%
“…Porcine cell lines that do not express CD46 were shown to be non-permissive to APPV infection, while porcine pestiviruses such as CSFV and BuPV efficiently infected these cells, indicating a CD46-independent mechanism of entry [ 15 ]. Additional binding partners of CSFV E2 have been identified and mapping of amino acids involved in these interactions has been achieved using yeast-two hybrid system [ 32 , 33 , 34 ]. These factors do not appear to play a role in virus entry, and the regions involved in these interactions fall outside the β-hairpin motif in domain II.…”
Section: Discussionmentioning
confidence: 99%